2014
DOI: 10.1371/journal.pone.0093731
|View full text |Cite
|
Sign up to set email alerts
|

Can Equids Be a Reservoir of Leishmania braziliensis in Endemic Areas?

Abstract: In this study, we detected Leishmania (Viannia) braziliensis infection in equids living in endemic regions of cutaneous leishmaniasis. To determine the role of these animals in the Leishmania cycle, we used two approaches: serological and molecular methods. Antibodies to the parasite were assayed using the Enzyme Linked Immunosorbent Assay (ELISA). Blood samples were collected and tested by polymerase chain reaction (PCR), and the positive products were sequenced. The results showed that 11.0% (25/227) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
(61 reference statements)
0
31
0
12
Order By: Relevance
“…in infected horses is common. Positive PCR with negative serology can be obtained in acute infection, or in some immune diseases (Truppel et al 2014). Asymptomatic cases of VL are common in dogs and humans, including seronegative dogs that can be PCR positives (Solano-Gallego et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in infected horses is common. Positive PCR with negative serology can be obtained in acute infection, or in some immune diseases (Truppel et al 2014). Asymptomatic cases of VL are common in dogs and humans, including seronegative dogs that can be PCR positives (Solano-Gallego et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Horses are commonly used for work in urban and rural areas of Brazil. Seropositive results from horses in Araçatuba/SP (Feitosa et al 2012) and in different countries from the state of Paraná (Vedovello-Filho et al 2008, Truppel et al 2014 suggest that horses likely attract sandflies that transmit leishmaniasis, because they probably serve as a source of blood. A study conducted in a CL endemic region of Brazil, the authors suggest that horses could be source of blood for phlebotomines in peridomestic environment and hence can be the primary reservoirs of L. (V.) braziliensis (Truppel et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among the investigations that have sought new possible reservoirs, there have been reports on equids showing clinical manifestations of cutaneous leishmaniasis (KOEHLER et al, 2002;SOLANO-GALLEGO et al, 2003;MÜLLER et al, 2009;SOARES et al, 2013). Furthermore, prevalence studies conducted in Europe (FERNÁNDEZ-BELLON et al, 2006;LOPES et al, 2013;SGORBINI et al, 2014), Asia (GAO et al, 2015AHARONSON-RAZ et al, 2015), Africa (MUKHTAR et al, 2000KENUBIH et al, 2015;ROHOUSOVA et al, 2015) and South America (AGUILAR et al, 1989;FEITOSA et al, 2012;TRUPPEL et al, 2014;OLIVEIRA et al, 2017;BENASSI et al, 2018) have demonstrated that horses (Equus caballus), donkeys (Equus asinus), mules (Equus asinus caballus) and ponies (E. caballus) are parasitized by different species of Leishmania, such as Leishmania braziliensis, Leishmania infantum and Leishmania siamensis, including cases of mixed infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is also not certain whether and which other domestic animals [42][43][44][45][46][47][48][49] and wild animals [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] play a role in this phenomenon in Suriname. Clearly, such efforts will both improve our understanding of leishmaniasis in Suriname and contribute to programs to combat this disease in the country.…”
Section: Future Directionsmentioning
confidence: 99%